Performance analysis and test of a maize inter-row self-propelled thermal fogger chassis - Chen, Liqing; Wang, Pinpin; Zhang, Peng; Zheng, Quan; He, Jin; Wang, Qingjie (International Journal of Agricultural and Biological Engineering, 2018)
In view of the difficulties in weeding and plant protection in the middle and late period of maize planting, this paper proposed a self-propelled thermal fogger chassis. According to the theoretical calculation and agronomic requirements for maize planting, the structure and working principles of the self-propelled thermal fogger chassis were introduced. On this basis, the multi-body dynamics model of chassis structure was established, and the chassis traction, steering and obstacle surmounting performances were also analyzed. Then the rationality and the feasibility of the design were verified through the furrow running test and test equipped with thermal fogger. Test results showed that, the traction performance improves with the decrease of soil deformation index and increase of cohesion, and when track pre-tensioning force was about 1000 N, the machine had a good traction performance; with the decrease of the soil deformation index and the increase of cohesive force, the stability of the single side brake turn of the chassis becomes better; on the contrary, with the increase of the tightness of the crawler, the steering radius turns smaller and the steering stability becomes worse. Under heavy clay, with the pre-tensioning of 1000 N, the machine has better steering stability and smaller turning radius. The obstacle-surmounting simulation result shows that on sandy soil road, the maximum climbing angle for the chassis is 42°, the height of vertical obstacle crossing is 170 mm and the trench width is 440 mm. The study provides a reference for the design of plant protection machinery in the middle and late stages of maize planting. Keywords: maize inter-rows, intelligent chassis, traction performance, steering performance, obstacle surmounting performance DOI: 10.25165/j.ijabe.20181105.3607 Citation: Chen L Q, Wang P P, Zhang P, Zheng Q, He J, Wang Q J. Performance analysis and test of a maize inter-row self-propelled thermal fogger chassis. Int J Agric & Biol Eng, 2018; 11(5): 100–107.